Avaliação de primatas da espécie Callithris Jacchus submetidos ao cativeiro - Ferraz, Myrna Campos [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The classical and instrumental conditioning using positive reinforcement applied to animals Callithrix jacchus were made with practicality and success. In this study the concentrations of salivary IgA in primate species Callithrix jacchus were very low. Since this species used as a model biological studies and being important in the immunoglobulin A and immune status check as an indicator to measure the stress in many animals including non-human primates suggest further studies using other techniques to quantify IgA in the saliva these animals. Possibly due to structural conditions and the lack of past animal, could not complete validation for physiological fecal glucocorticoid metabolites in the species under study. Thus to obtain reliable results in studies using these animals as an experimental model, it is necessary to have a structure against cold and heat, as well as keep the animals protected site visitors, sounds and other animals. Furthermore, there is a need to know the history of animals and the use of a known strain with cohesive colony. The commercial kits from Cayman Chemical ® for detection of progesterone and estradiol in human plasma used in this study for the determination of fecal metabolites of progesterone and estradiol Callithrix jacchus were validated both as laboratory physiologically allowing thereby detect increases or decreases in the concentration of progesterone during the cyclic ovarian activity during pregnancy and also as detecting increases and decreases in the concentration of estradiol in the periods before, during and after pregnancy. The management of the supply of raw propolis Callithrix jacchus aided in weight gain of males and females before the gestational period besides having collaborated in maintaining weight during pregnancy treated group of females, thus suggesting a better feed conversion. Because of the difference in the behavior of animals in days when no stressful events occurred and due to...

Os condicionamentos clássico e instrumental com a utilização de reforço positivo aplicados aos animais da espécie Callithrix jacchus foram efetuados com praticidade e sucesso. Neste estudo as concentrações da IgA salivar na espécie de primatas Callithrix jacchus foram muito baixas. Sendo essa espécie utilizada como modelo biológico em diversos estudos e sendo a imunoglobulina A importante na verificação do status imunológico e como indicadora para medir o estresse em vários animais incluindo primatas não humanos, sugerimos novos estudos utilizando outras técnicas para a quantificação da IgA presente na saliva destes animais. Possivelmente devido às condições estruturais e ao desconhecimento do histórico dos animais, não foi possível concluir a validação fisiológica para os metabolitos fecais de glicocorticóides na espécie em estudo. Sendo assim para obter resultados fidedignos em pesquisas utilizando estes animais como modelo experimental, se faz necessário possuir estrutura contra frio e calor intenso, assim como manter os animais em local protegido de visitantes, sons e outros animais. Além disso, existe a necessidade do conhecimento do histórico dos animais e da utilização de uma colônia coesa com linhagem conhecida. Os conjuntos comerciais da Cayman Chemical® para a detecção de progesterona e estradiol em plasma humano utilizado nesse estudo para dosagem de metabólitos fecais de progesterona e estradiol em Callithrix jacchus foram validados tanto fisiologicamente quanto laboratorialmente permitindo desta forma, detectar aumentos e diminuições nas concentrações da progesterona durante a atividade cíclica ovariana e na fase gestacional como também detectar aumentos e diminuições nas concentrações de estradiol nos períodos antes, durante e após as gestações. A administração da própolis bruta na alimentação de Callithrix jacchus auxiliou no ganho de peso de machos e fêmeas antes do período..
Keywords: Primatas - Reprodução; Animais silvestres em cativeiro; Reprodução animal; Estudos de validação; Validation Studies